(3JMUjd dHGH GdMceIs - (3HgefjGQ Hf GdeQRHGf GdGPQHjLGf, CHh GdMSf,J (B458 (3g` s; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3bGd HgejfGQ Hf GdeQRHGf HYO MeO Gddg agPg GdQSGdI ddNGd Ci efUhQ HgQGe Hf NQTjO dHGH GdMceI GdJi gPHgG CHh Ydi GdMSjf Hf YHO Gddg Hf SjfG ebJOjG HGdJQJjH HGdMceI s
(3BNQgG (B:s
(3abO YQafG MGd GdfahS GdebGHdI ai eYGOgG hCeG NGd SGFQ GdfahS adGSHjd Edi eYQaI CMhGdgG HGdHQgGf heO GdHOf ef GdMceI EPG Mce Sgd SHjd eG HYOg ef GdJhajb hGdJaVjd hGdHSW hGdJMbjb hfSFd Gddg GdJhajb s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs